2014
DOI: 10.1007/s00464-014-3419-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and converted approaches to rectal cancer resection have superior long-term outcomes: a comparative study by operative approach

Abstract: LAP and converted procedures have comparable or superior clinical and oncologic outcomes. More procedures should be approached through a LAP approach. If the procedure cannot be completed laparoscopically, outcomes are not compromised for converted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…19 Perioperative complications, evaluated by ICD-9-CM codes from the NIS database, are equivalent, if not lower than previous reports, and this might be a result of increased surgeon experience. 2,4,5,20 The rate of a laparoscopic converted to an open APR in this study was low. This may be secondary to the implementation of robotic assistance or the use of hand-assisted laparoscopy.…”
Section: Commentsmentioning
confidence: 59%
See 4 more Smart Citations
“…19 Perioperative complications, evaluated by ICD-9-CM codes from the NIS database, are equivalent, if not lower than previous reports, and this might be a result of increased surgeon experience. 2,4,5,20 The rate of a laparoscopic converted to an open APR in this study was low. This may be secondary to the implementation of robotic assistance or the use of hand-assisted laparoscopy.…”
Section: Commentsmentioning
confidence: 59%
“…3,4 These trials demonstrated significant benefits with the laparoscopic approach including a reduction in postoperative ileus, decreased length of stay (LOS), lower risk of a nonroutine discharge, and a reduction in cost. 2,5 Comparable results have also been demonstrated in laparoscopic cases that were converted to open and those using a small ''minilaparotomy.'' 9 These studies also advocate attempting laparoscopy for most colorectal cancers regardless of disease stage.…”
mentioning
confidence: 68%
See 3 more Smart Citations